Comparative characteristics of psychophysiological features skilled basketball players-women with hearing and skilled basketball players healthy - Kozina Zh.L; Sobko I.N; Klimenko A.I; Sak N.N (Kharkov National Pedagogical University, 2013)
A comparative analysis of the psychophysiological features of skilled basketball players with normal hearing and impaired hearing aid. The study involved two women's basketball team to 12 people each. The study used a complex computer psychodiagnosis. The complex includes 20 psychophysiological and 18 personal psychological tests. The indicators of the time simple and complex reaction and average tapping test healthy skilled basketball players and basketball players are hearing impaired. There was a significant higher rates of visual-motor speed and reaction-tapping test in basketball players with hearing compared to healthy athletes. This is explained by compensatory mechanisms that occur in connection with the violation of the audition.